Metode Pendidikan dalam Al-Qur'an dan Hadis: Implementasi dalam Konteks Pendidikan Modern - Moh Restu Hoeruman; Achmad Zuhri; Muhammad Shaleh Assingkily; Nurul Fauziah; Deni Fikari (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to examine the educational methods found in the Qur'an and Hadith, as well as the approaches used by the Prophet Muhammad in the learning process and character development of the Muslim community. This research employs a qualitative method with a literature review approach, collecting and analyzing various Qur'anic verses and Hadith related to education. The findings indicate that Islamic educational methods encompass various approaches, such as the dialogue and question-and-answer method, the exemplary method (uswah hasanah), storytelling, direct practice (learning by doing), and the method of repetition and habituation. The Prophet Muhammad implemented these methods with wisdom and gentleness, adapting his approach to the conditions and needs of his people. The study concludes that education in Islam is not solely focused on knowledge transfer but also on building character, morality, and spirituality. The educational methods exemplified by the Prophet Muhammad (PBUH) remain highly relevant in modern educational contexts, serving as a valuable guide for Muslim educators in designing effective learning systems aligned with Islamic values.